Hedging modal adverbs in Slovenian academic discourse - Jakob Lenardič; Darja Fišer (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave, 2021)
This paper first presents a comparative analysis of modal adverbs in doctoral theses in the humanities and social sciences on the one hand, and in natural and technical sciences on the other from the 1.7-billion-token corpus of Slovenian academic texts KAS (Erjavec et al., 2019a). Using a randomized concordance analysis, we observe the epistemic and non-epistemic usage of the modal adverbs and show that epistemic adverbs are more characteristic of the humanities and social sciences theses. We also show that the non-epistemic dispositional meaning of possibility, which is most commonly used in natural and technical sciences theses, is not used as a hedging device. In the second part of the paper we compare the usage of a selected set of modals in bachelor’s, master’s and doctoral theses in order to chart how researchers’ approach to stance-taking changes at different proficiency levels in academic writing, showing that the observed increase in hedging devices in doctoral theses seems to be less a function of an increased proficiency level in academic writing as such and more the result of conceptual differences between undergraduate and postgraduate theses, only the latter of which are original research contributions with extensive discussion of the results.